(untitled) (Desenvolvimento em Questão, 2020)
The Golden Rule, established in Brazil by article 167 of the Federal Constitution of 1988, aimed to improve the quality of public spending, avoiding an increase in current expenses financed by the assumption of credit operations. However, up to the year 2000, there is a constant fiscal imbalance in the country, that is, spending remained higher than revenues, directly impacting economic growth. In this context, Complementary Law 101, known as the Fiscal Responsibility Law (LRF), was defined in 2000, defining criteria, conditions and limits for budgetary, financial and asset management and implementing new mechanisms for controlling public expenditures. However, how the Golden Rule was implemented in Brazil allows it to be fulfilled even with the indebtedness growing well above public investments. This is because the high volume of financial revenues available to the Brazilian federal government, among them, the positive result of the Central Bank transferred to the National Treasury, contributes to its fulfillment. In this sense, the objective of this article is to analyze the impacts of the transfer of the results of the Central Bank, in the period from 2008 to 2017, in compliance with the Golden Rule in Brazil. The analysis shows that, especially from 2010 onwards, the transfer of operating income and the foreign exchange operations of the Central Bank to the National Treasury contributed to the National Treasury demonstrating compliance with the Constitutional mandate. However, as a consequence, the control of public indebtedness and fiscal balance was impaired.